PREGNANT WOMEN GROUPS: KNOWLEGES, CHANGES AND LINKS OF SPAPE AMONG THE PARTICIPANTS - Isabel Cristina Pacheco Van der Sand; Graziele Strada Sartori (Universidade Federal de Goias, 2004)
During pregnancy there are several changes and consequent adaptations that might produce anxietyand fear. A form of confronting might be the participation in pregnant women groups. This study wants to know theperception of the participants in pregnant women groups and its repercussion in the womens lives after themeetings. It is a study with qualitative, descriptive and exploratory approach, of the case study kind. The data weregathered through non-structured interviews. For the analysis the proposition of Bardin was taken into consideration.Two out of four emergent themes two are presented in this article: the group as a space of knowledge, changesand links; and, the group and the repercussions in the participants lives. The pregnant women groups can betherapeutic for their participants and they pertinent while integral form to assistance people.